THE ROLE OF SOCIAL SUPPORT FACTORS IN THE DEVELOPMENT OF ELITE FOOTBALL PLAYERS - Nooraini Hamzah; Zulakbal Abd Karim; Jeffrey Low Fook Lee; Abd Rahim Mohd Shariff; Junaidy Mohamad Hashim, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This concept paper will discuss the factors that may have an impact on the player's performance in achieving an elite level within the context of football. There are many factors that influence the development and performance of football players in reaching elite levels. These include physical, technical, tactical, psychological and social factors. In terms of social components, parents, siblings, teachers, coaches, training facilities, and the environment are factors that may influence performance. Therefore, the primary aim of this concept paper is to investigate the impact of social and environmental support factors on elite players, particularly in football. Previous research has found that social factors such as parental and coach support may influence the player’s performance in reaching the elite level. Additionally, another factor that is still debated is the role of the training environment for football players. Suitable and conducive facilities and environments have been found to improve the player’s performance in achieving the elite level. The findings obtained will help in producing a conceptual framework of social support factors and training environment facilities that play an important role in influencing athlete performance in football.